IMPROVING TEACHER COMPETENCY IN IMPLEMENTING LEARNING METHODS BASED ON ACTIVITY THROUGH PEER TUTORS AT UPT SD NEGERI JATEN, WONODADI DISTRICT, BLITAR DISTRICT - Wulandari; Isna Nurul Inayati (EBTIDA': Jurnal Pendidikan Dasar Islam, 2022)
The results of the Analysis of Quality Report Cards in SD Negeri Jaten show that one of the low educational standards is the process standard. This is reinforced by the results of observations which show that some teachers at these schools do not yet have the ability to properly prepare activity-based lesson plans. For this reason, it is necessary to increase teacher competency in the implementation of active learning through peer tutors. This type of research is school action research. This research was conducted at SD Negeri Jaten in November 2021 with the research subjects being all SD Negeri Jaten teachers. The techniqueof collecting data from this school action research is through qualitative data obtained from observation/observations, interviews and document studies. This procedure includes the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The results showed that in general the quality of the implementation of activities to increase teacher competence in preparing lesson plans using active learning methods had increased and the impact of these activities had quite a positive effect on student well-being.